Pollution Reduction Preferences of U.S. Environmental Managers: Applying Ajzen'S Theory of Planned Behavior - Cordano, Mark; Frieze, Irene Hanson (Academy of Management Journal, 2000)
We modified Ajzen's theory of planned behavior to analyze the behavioral preferences of environmental managers. We used structural equation analysis to link the source reduction preferences of 295 environmental managers to their pollution prevention attitudes, their perceptions of norms for environmental regulation, their perceived behavioral control, and the past source reduction activity of their facilities. The hypothesized model fit the data well, except that we found the perceived behavioral control variable was negatively rather than positively predictive of behavioral preferences for source reduction activity. Research and practical implications are suggested.